Fairness and Cheating - Stefan Vetter; Daniel Houser; Joachim Winter (Verein für Socialpolitik, 2010)
We present evidence from a laboratory experiment that individuals who feel having been treated unfairly in the interaction with others are more likely to cheat in a subsequent, unrelated game. We interpret this result as showing that the violation of a social norm (fairness) by others can be sufficient to justify a norm violation at the expense of a third party. This result extends the growing literature on social norms. Furthermore, we also find tentative evidence that cheating is correlated with social preferences.
Keywords: C91; D63; C90; 330; cheating; social norms; experimental design